Multiple Roles of the Y Chromosome in the Biology of Drosophila melanogaster - Roberto Piergentili (The Scientific World Journal)
The X and Y chromosomes of Drosophila melanogaster were the first examples of chromosomes associated with genetic information. Thanks to the serendipitous discovery of a male with white eyes in 1910, T.H. Morgan was able to associate the X chromosome of the fruit fly with a phenotypic character (the eye color) for the first time. A few years later, his student, C.B. Bridges, demonstrated that X0 males, although phenotypically normal, are completely sterile. This means that the X chromosome, like the autosomes, harbors genes that control several phenotypic traits, while the Y chromosome is important for male fertility only. Notwithstanding its long history – almost 100 years in terms of genetic studies – most of the features of the Y chromosome are still a mystery. This is due to the intrinsic nature of this genetic element, namely, (1) its molecular composition (mainly transposable elements and satellite DNA), (2) its genetic inertia (lack of recombination due to its heterochromatic nature), (3) the absence of homology with the X (with the only exception of the nucleolar organizer), (4) the lack of visible phenotypes when it is missing (indeed, except for their sterility, X0 flies are normal males), and (5) its low density as for protein-coding sequences (to date, only 13 genes out of approximately 14,000 have been mapped on this chromosome in D. melanogaster, i.e., ~0.1% of the total). Nonetheless, a more accurate analysis reveals that this chromosome can influence several complex phenotypes: (1) it has a role in the fertility of both sexes and viability of males when over-represented; (2) it can unbalance the intracellular nucleotide pool; (3) it can interfere with the gene expression either by recruiting proteins involved in chromatin remodeling (PEV) or, to a higher extent, by influencing the expression of up to 1,000 different genes, probably by changing the availability of transcription factors; (4) it plays a major role (up to 50%) in the resistance to heat-induced male sterility; (5) it affects the behavior; and (6) it plays a role in genetic imprinting. In the present paper, all these Y-related phenotypes are described and a potential similarity with the human Y chromosome is drawn.